RANCANG BANGUN TEMPAT SAMPAH PINTAR PADA RUMAH TANGGA BERBASIS IOT DAN ANDROID - Ahmad Farid Hidayat; Andin Eka Safitri (Journal of Research and Publication Innovation, 2024)
Human life is increasingly dynamic, making them carry out various efforts and activities to meet the needs of life. This has a very impact on waste production which continues to increase as a result of these activities carried out. Households are the largest contributors to waste compared to other industrial sectors. Sorting organic and inorganic waste needs to be done in order to minimize environmental pollution caused. The research method used to create IoT and Android-based smart bins is the R&D (Research and Development) method. R&D is a process or steps to develop a new product or improve an existing product. This research will create a waste bin that can sort organic and inorganic waste automatically. It is hoped that the design of the smart trash can provide a warning when the trash can is full to the garbage officers so that they can transport the garbage regularly.